The Effectiveness of Career Guidance Programs on Career Maturity and Employability of Fashion Design Students - Novia Ira Maulana; Tuwoso; Hery Suswanto (Indonesian Scientific Publication, 2026)
The transformation of the global fashion industry driven by digital design technologies, platform-based marketing, sustainability imperatives, and expanding entrepreneurial opportunities has reshaped the competency profile expected of graduates in fashion education. In response, career guidance has become an increasingly important mechanism for supporting students’ transition from education to professional practice. This systematic literature review examines the role of career guidance programs in fostering career maturity and employability within vocational and fashion-oriented higher education. Career guidance programs in this review refer to structured interventions such as career counseling, employability skills modules embedded in curricula, mentoring initiatives, internship preparation, and portfolio-based career development activities. Using a PRISMA-guided systematic selection process across major academic databases, 23 empirical studies published between 2015 and 2025 were analyzed. The findings identify three dominant approaches: developmental career guidance grounded in career development theory, competency-based employability programs, and experiential models integrated with industry engagement. The evidence indicates that structured and sustained career guidance interventions are associated with improvements in vocational goal clarity, decision-making confidence, career planning skills, job-search competence, and perceived employability. Programs incorporating internships, mentoring, and portfolio development tend to demonstrate stronger employability-related outcomes than counseling-only approaches. The synthesis further suggests a sequential pathway in which career guidance strengthens psychological readiness (career maturity), which subsequently contributes to behavioral preparedness and employability outcomes. However, the evidence base remains largely cross-sectional and relies heavily on self-reported outcomes, with limited longitudinal data on objective employment results. Overall, the review supports the development of an integrated, industry-aligned career guidance model tailored to vocational and fashion education contexts.